Reactive Balance Responses After Mild Traumatic Brain Injury: A Scoping Review. Issue 5 (1st September 2022) - Morris, Amanda; Casucci, Tallie; McFarland, Mary M.; Cassidy, Benjamin; Pelo, Ryan; Kreter, Nicholas; Dibble, Leland E.; Fino, Peter C.
Abstract : Objective: Balance testing after concussion or mild traumatic brain injury (mTBI) can be useful in determining acute and chronic neuromuscular deficits that are unapparent from symptom scores or cognitive testing alone. Current assessments of balance do not comprehensively evaluate all 3 classes of balance: maintaining a posture; voluntary movement; and reactive postural response. Despite the utility of reactive postural responses in predicting fall risk in other balance-impaired populations, the effect of mTBI on reactive postural responses remains unclear. This review sought to (1) examine the extent and range of available research on reactive postural responses in people post-mTBI and (2) determine whether reactive postural responses (balance recovery) are affected by mTBI. Design: Scoping review. Methods: Studies were identified using MEDLINE, EMBASE, CINAHL, Cochrane Library, Dissertations and Theses Global, PsycINFO, SportDiscus, and Web of Science. Inclusion criteria were injury classified as mTBI with no confounding central or peripheral nervous system dysfunction beyond those stemming from the mTBI, quantitative measure of reactive postural response, and a discrete, externally driven perturbation was used to test reactive postural response. Results: A total of 4747 publications were identified, and a total of 3 studies (5 publications) were included in the review. Conclusion: The limited number of studies available on this topic highlights the lack of investigation on reactive postural responses after mTBI. This review provides a new direction for balance assessments after mTBI and recommends incorporating all 3 classes of postural control in future research.